2022
DOI: 10.3390/antibiotics11121825
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Phenotypic Antimicrobial Resistance among ESKAPE Bacteria and Enterobacterales Strains in Wild Birds

Abstract: Antimicrobial resistance (AMR) is a current public health issue globally. To counter this phenomenon and prioritize AMR in the health sector, the World Health Organization (WHO) published a list of bacterial pathogens against which the development of new antimicrobial agents is urgently needed, designating the ESKAPE pathogens (i.e., Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) with a ‘priority status’. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…The group is known as ESKAPE as it comprises of following bacteria: Enterococcus faecium , S. aureus , Klebsiella pneumoniae , Acinetobacter baumannii , P. aeruginosa , and Enterobacter species . These bacterial pathogens are accountable for numerous nosocomial infections and human mortality . These bacteria possess the ability to form biofilms with a protective EPS that makes these pathogens antibiotic resistant.…”
Section: Overview Of Biofilm Formation On Medical Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The group is known as ESKAPE as it comprises of following bacteria: Enterococcus faecium , S. aureus , Klebsiella pneumoniae , Acinetobacter baumannii , P. aeruginosa , and Enterobacter species . These bacterial pathogens are accountable for numerous nosocomial infections and human mortality . These bacteria possess the ability to form biofilms with a protective EPS that makes these pathogens antibiotic resistant.…”
Section: Overview Of Biofilm Formation On Medical Implantsmentioning
confidence: 99%
“…40 These bacterial pathogens are accountable for numerous nosocomial infections and human mortality. 41 These bacteria possess the ability to form biofilms with a protective EPS that makes these pathogens antibiotic resistant. They enter the body either during medical procedures or from bacteria present on the skin leading to nosocomial infection and infection of medical devices or implants.…”
Section: Introductionmentioning
confidence: 99%
“…Although wild birds are infrequently exposed to antimicrobial agents, their faecal waste might function as reservoirs and potential disseminators of resistant bacteria in the environment [ 4 ]. It is believed that birds contract resistant bacteria from humans and other sources by consuming infected food or water [ 3 ]. Antibiotic residues and bacteria expressing antibiotic resistance may enter the environment as a result of the spread of medicated animal manure and urban effluents into agricultural land [ 191 ].…”
Section: Antimicrobial Resistance Profiles Of Bacteria Isolated From ...mentioning
confidence: 99%
“…This creates the potential for the establishment of novel foci of emerging or re-emerging communicable diseases along bird migration routes [ 2 ]. Birds, in particular free-living birds, have been widely reported as reservoirs of pathogens and, due to their ability to occupy different ecological niches and to adapt to many urban, suburban, and livestock environments, represent true sentinels [ 3 ]. Numerous studies conducted worldwide have reported the presence of various bacteria in wild birds, many of which may have a high zoonotic potential [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ESKAPE group (Figure ) is a collection of six genera that are responsible for a range of nosocomial infections . These organisms include both Gram-positive and Gram-negative bacteria.…”
Section: Biofilm-forming Pathogens and Their Significancementioning
confidence: 99%